ANALISIS CVP (COST VOLUME PROFIT) UNTUK PERENCANAAN LABA PADA CV. ZAM-ZAM COLLECTION KABUPATEN JOMBANG - Sa’adah, Lailatus; Azizah, Indy Asna (Universitas Wiralodra, 2023)
This study aims to determine the calculation of profit planning on CV. Zam-Zam Collection as a whole uses cost-volume-profit analysis (CVP) with reference to the last year, that’s on 2022. The research method with primary data sources and secondary data. From the results of reseacrh in 2022 CV. Zam=Zam managed to sell 10.211 headscarves, earning Rp. 304.447.000. While the variable cost incurred are Rp. 233.780.490. and a fixed fee of Rp. 17.961.250. From the results of these calculations, the contribution margin result is Rp. 70.666.510 and the contribution margin ratio is 23%. The break even point result is IDR 78.092.781 and the BEP unit is 1.150 pcs. Result Margin of Safety of Rp. 226.354.609 with a percentage ratio of 74.35% the operating laverage is 1,34. Based on the calculation results of the cost-volume-profit (CVP) analysis, it shows that CV. Zam-Zam Collection has not yet carried out profit planning, but judging from the profit target with the reality of the profit generated, CV. Zam-Zam Collection has been able to achieve it.